EXPERT NORMS FOR DEALING WITH STUDENTS’ MATHEMATICAL THINKING IN DIFFERENT CULTURES - Dreher, Anika; Lindmeier, Anke; Feltes, Paul; Wang, Ting-Ying; Hsieh, Feng-Jui (Proceedings of the International Group for the Psychology of Mathematics Education, 2021)
There is a growing interest in the international mathematics education community in research on teacher noticing as an important component of teaching expertise. However, it is likely that often the researchers’ understanding of good instructional quality influences what they expect teachers to notice. It is particularly not clear if and how different cultural norms of instructional quality influence how teacher noticing is operationalized in East Asian and Western cultures. Therefore, our crosscultural research project on teacher noticing in Taiwan and Germany focuses in a first step on eliciting such expert norms. By means of a vignette-based online expert survey, we explored culture-specific norms regarding instructional quality. In this paper, we provide evidence of culturally different norms for dealing with students’ thinking.
CRIS-Team Scopus Importer:2024-10-02